2006
DOI: 10.1007/s10433-006-0025-1
|View full text |Cite
|
Sign up to set email alerts
|

Stability and change in physical activity in old age: the role of changes in disability

Abstract: The objective was to examine whether stability and change in physical activity in older men and women are influenced by (1) changes in disability and by (2) social relations and psychological well-being. The study is based on baseline, 3 and 4.5 year follow-up data on 917 older men and women. Changes in physical activity were measured through self-reported frequencies of vigorous physical activity at the three measurement points. The analyses were carried out for two outcomes-decline in physical activity versu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 47 publications
1
5
0
Order By: Relevance
“…Comparing with gender, it emerged that women engaged in less physically activity than men (42). Our study results and those of others confirm that while "walking" is one of the most common forms of physical exercise practised by older persons (43), it is watching TV that most occupies their leisure time (44).…”
Section: Discussionsupporting
confidence: 75%
“…Comparing with gender, it emerged that women engaged in less physically activity than men (42). Our study results and those of others confirm that while "walking" is one of the most common forms of physical exercise practised by older persons (43), it is watching TV that most occupies their leisure time (44).…”
Section: Discussionsupporting
confidence: 75%
“…[43] A study on 75-and 80-year-old persons in four counties in Denmark showed that older adults who developed mobilityrelated fatigue or who continuously felt fatigue when performing their daily activities during 4.5 years were more likely to show a concurrent decline in their physical activities during the same period. [44] In another study based on the NORA data it was shown that women with mobility-related fatigue at age 75 had fewer social network activities compared with women without fatigue, i.e., they had little sustained contact with children and little sustained diversity in social relations over the next five years. [45] Underlying factors Numerous studies have investigated the underlying factors for fatigue in patients (for a review see [1]).…”
Section: Fatigue: Biomedicine Health and Behaviormentioning
confidence: 99%
“…Results from cross-sectional data from the 70-year study in Glostrup showed that men and women with a low score on the Mob-T Scale were more likely to be less active with regard to physical, intellectual, cultural and social activities, compared with persons with high scores on the scale (66). A study on 75-and 80-year old persons in four counties in Denmark showed that older adults who developed fatigue or who continuously felt fatigued when performing their daily activities during 4½ years were more likely to show a concurrent decline in their physical activities during the same period (67). It was also shown that women who felt fatigued in their daily activities at age 75 had fewer social network activities compared with non-fatigued women, …”
Section: Fatigue As a Predictor Of Other Outcomesmentioning
confidence: 99%